Mandatory sick pay provision: a labor market experiment - Bauernschuster, Stefan; Dürsch, Peter; Oechssler, Joerg; Vadovič, Radovan (Jena economics research papers, 2009)
The question whether a minimum rate of sick pay should be mandated is much debated. We study the effects of this kind of intervention in an experimental labor market that is rich enough to allow for moral hazard, adverse selection, and crowding out of good intentions to occur. We find that higher sick pay is reciprocated by workers through higher effort but only if sick pay is not mandated. We also study adverse selection effects when workers have different probabilities of getting sick and can reject the hypothesis that this leads to market breakdown. Overall, we find that mandating sick pay actually leads to a higher voluntary provision of sick pay by firms. -- sick pay ; sick leave ;experiment ; gift exchange.